Bery Engebretsen letter to Carl J. Bendorf regarding bird sightings, December 1, 1988 - Engebretsen, Beryet al (1988)
Field notes contributed by Bery Engebretsen in a letter to Carl J. Bendorf with observer Stephen J. Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed